ABO and Rhesus (D) blood group distribution among blood donors in rural south western Uganda: a retrospective study. (December 2016) - Apecu, Richard; Mulogo, Edgar; Bagenda, Fred; Byamungu, Andrew
Abstract Background In Uganda, geographical distribution of blood groups and Rhesus (D) factor varies across the country. The aim of this study was to examine the distribution of these groups among voluntary blood donors in rural southwestern Uganda. Results Twenty-three thousand five hundred four (23, 504) blood donors were included in the study. The donors had a mean age of 21 years (SD ± 5.7) and were mainly male (73%). The distribution of ABO blood group was; blood group O (50.3%); blood group A (24.6%); blood group B (20.7%) and blood group AB (4.5%). The proportions of Rhesus (D) positive and Rhesus (D) negative were 98 and 2% respectively. The proportion of non-adult donors (<18 years) was significantly higher among the female than the male donors (p value <0.001). A significantly higher proportion of males than females were Rhesus (D) negative (p-value <0.001). No significant relationship was found between age and blood group distribution. Conclusion The sequence of ABO distribution among the rural population in southwestern Uganda is; O > A > B > AB, with males as the predominant donors. The frequency of Rhesus (D) negative is very low in rural southwestern Ugandan and is mainly among males. The blood bank services in southwestern Uganda need to develop innovative strategies targeting female donors who are more likely to boost blood stocks in the region.